1999
DOI: 10.1161/01.res.85.11.1092
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Cardiac β 2 -Adrenergic Signal Transduction

Abstract: Recent studies have added complexities to the conceptual framework of cardiac beta-adrenergic receptor (beta-AR) signal transduction. Whereas the classical linear G(s)-adenylyl cyclase-cAMP-protein kinase A (PKA) signaling cascade has been corroborated for beta(1)-AR stimulation, the beta(2)-AR signaling pathway bifurcates at the very first postreceptor step, the G protein level. In addition to G(s), beta(2)-AR couples to pertussis toxin-sensitive G(i) proteins, G(i2) and G(i3). The coupling of beta(2)-AR to G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
169
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(177 citation statements)
references
References 84 publications
5
169
0
3
Order By: Relevance
“…Inherent in the clinical discussion is recent molecular insight into differences between cardiac ␤ 1 -and ␤ 2 -adrenoreceptor stimulation at the signal-transduction level (10,11). In rat cardiomyocytes, a ␤ 2 -agonist, zinterol, was shown to increase calcium current in a manner qualitatively distinct from ␤ 1 -adrenoreceptor stimulation (12), consistent with single-channel effects reported later (13).…”
supporting
confidence: 61%
“…Inherent in the clinical discussion is recent molecular insight into differences between cardiac ␤ 1 -and ␤ 2 -adrenoreceptor stimulation at the signal-transduction level (10,11). In rat cardiomyocytes, a ␤ 2 -agonist, zinterol, was shown to increase calcium current in a manner qualitatively distinct from ␤ 1 -adrenoreceptor stimulation (12), consistent with single-channel effects reported later (13).…”
supporting
confidence: 61%
“…30,31,33,37 Recent studies in rodent cardiomyocytes revealed that b 2 -receptors couple to G-proteins, which lead to inhibition of cyclic AMP formation downstream. 38,39 In the ischaemic myocardium, the Na + /H + exchanger, which itself is under the influence of the C825T polymorphism, 3,4 exerts an important modulatory action on cardiac excitation-contraction coupling. 36 Published studies on the possible influence of the GNB3 C825T polymorphism reported inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…This promotes the influx of calcium into the cytosol of the cardiomyocyte, causing actin-myosin myofibrillar cross-linking, which results in cellular contraction (Fig. 2) [44].…”
Section: Systolic Dysfunctionmentioning
confidence: 99%